Longitudinal assessment of hand and axial bone mineral density in rheumatoid arthritis: A comparison of bone mineral density changes in early versus late disease - Ozgocmen, S; Ardicoglu, O; Kamanli, A; Kaya, A (Springer London Ltd, 2004)
[Abstract Not Available]
IOF World Congress on Osteoporosis -- MAY 14-18, 2004 -- Rio de Janeiro, BRAZIL